2017
DOI: 10.1016/j.jcm.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of Pain Management Manipulative Therapy for Knee Osteoarthritis With the Squeeze-Hold Technique: A Case Series

Abstract: Objective: The purpose of this case series was to describe the short-term and long-term clinical effects of a manual technique for treating osteoarthritis (OA) knee pain. Methods: This study measured of the immediate effect and long-term effect by using a case series of different groups of subjects. Knee OA and activity restriction in patients were evaluated by using the Kellgren-Lawrence (K/L) Grading Scale and the Japanese Knee Osteoarthritis Measure (JKOM) index. In the intervention, lower limb muscles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In line with our hypothesis, Chiu et al [10] validated FSN effectiveness in reducing skeletal muscle hardness around the knee and alleviating knee pain, Nakajima [11,12] demonstrated that increasing blood flow and reducing stiffness in lower limb muscles could relieve knee pain. Building on this, considering the physiological heterogeneity in individual muscles, a self-controlled before-and-after study design with unilateral knee osteoarthritis (KOA) patients was deemed most suitable for our small-sample exploratory pilot trial.…”
Section: Introductionsupporting
confidence: 82%
“…In line with our hypothesis, Chiu et al [10] validated FSN effectiveness in reducing skeletal muscle hardness around the knee and alleviating knee pain, Nakajima [11,12] demonstrated that increasing blood flow and reducing stiffness in lower limb muscles could relieve knee pain. Building on this, considering the physiological heterogeneity in individual muscles, a self-controlled before-and-after study design with unilateral knee osteoarthritis (KOA) patients was deemed most suitable for our small-sample exploratory pilot trial.…”
Section: Introductionsupporting
confidence: 82%
“…Even after 10 min of opening, StO 2 remained higher than at rest at 74.3 ± 5.5%. In Nakajima's manual compression therapy, StO 2 at rest was 60.1 ± 5.7%, and after the intervention, StO 2 was 65.3 ± 4.8%-an increase of about 10% [6]. Intervention with the pneumatic cuff is thought to have the same level of effect on promoting muscle blood flow as manual compression therapy by Nakajima.…”
Section: Discussionmentioning
confidence: 93%
“…This method involves manually applying pressure to the muscle and holding it there for a period of time. Nakajima reported that when this new method was applied to patients with OA of the knee, it promoted muscle blood flow and provided excellent pain relief [6]. On the other hand, Knee OA affects a large number of people [7].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Young's modulus of the QT in the AS pain group was significantly increased; Young's modulus of the PT in the AI pain group was significantly increased; Young's modulus of the MCL in the ME pain group was significantly increased; and Young's modulus of the LPR in the LA pain group were significantly increased in patients. In addition, Nakajima used a manipulative therapy to treat knee OA by squeezing the lower limb muscles by hand, and found that the pain can be effectively alleviated by changing the mechanical properties of muscles [39]. The results obtained in this study will provide better guidance and help for follow-up knee pain relief and more targeted rehabilitation treatment.…”
Section: Discussionmentioning
confidence: 76%